Financial Sector Assessment : Lebanon - World Bank (Washington, DC, 2014)
Lebanon's very large banking system has inhibited the emergence of capital markets. The country's licensing regime grants banks ipso facto authorization to engage in the full range of capital market activities. The authorities have embarked on developing new capital market channels for intermediating saving and investment to complement and compete with banking. The aim is to enrich financing choices, particularly long-term risk capital, to support private sector initiative and jobs that come with sustainably higher growth. The ultimate outcome will be better allocation and monitoring of capital. An element of this strategy is to establish a credible regulator of such financial intermediation. Law 161, enacted in 2011, created the Capital Markets Authority (CMA) which is soon to launch operations. A respected regulator is only one element of a master plan to nurture capital market functionalities that meet the needs of private companies and the country's infrastructure program. Market development will be a long-range balancing act between financial innovation and prudent oversight in the peculiar context of Lebanon. The insurance sector is material compared to other markets in the region but small by international standards. Insurers generally have sufficient expertise to operate current business models but weaknesses should be addressed in risk identification and management. Despite severe legal limitations, the Insurance Control Commission (ICC) has grown in stature and respect, and has taken full advantage of areas where improvements can be made through regulation. The sector's further development hinges on passing the new draft law pending in Parliament.